Effect of coupling agent on mechanical properties of composite from microcrystalline cellulose and recycled polypropylene - Jaafar, Awanis; Sofian, Anis Sofia; Samat, Noorasikin (Trans Tech Publications, Switzerland, 2012)
This study shows the effect of using 3-aminopropyltriethoxysilane (APS) and maleic anhydride-grafted polypropylene (MAPP) as coupling agent on composite of RPP/MCC fiber. The compositions of MCC were varied from 0, 2, 4, 8 and 12 wt%. The compounded samples were prepared into test specimens by using injection moulding. The RPP/MCC composites with and without the coupling agent were characterized through mechanical testing of flexural and impact test. The incorporation of the modified MCC was found to increase the modulus and flexural strength. The flexural test indicates that the addition of 4 wt% MCC-APS and 8 wt% MCC-MAPP significantly increased the flexural strength of the RPP composite compared to the unmodified MCC. The impact test shows higher impact strength at 4 wt% of RPP/MCC-APS and 2 wt% of RPP/MCC-MAPP, respectively